2016
DOI: 10.1007/5584_2016_2
|View full text |Cite
|
Sign up to set email alerts
|

Russian Kefir Grains Microbial Composition and Its Changes during Production Process

Abstract: By combining DGGE-PCR method, classical microbiological analysis and light- and electron microscopic observations, it was found that the composition of microbial communities of central Russia regions kefir grains, starter and kefir drink include bacteria of the genera Lactobacillus, Leuconostoc and Lactococcus, and yeast anamorphs of the genera Saccharomyces, Kazachstania and Gibellulopsis. Fifteen prokaryotic and four eukaryotic pure cultures of microorganisms were isolated and identified from kefir grains. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 31 publications
1
20
0
6
Order By: Relevance
“…It is unclear what causes the microbiota of kefir to form such a stable consortium that maintains its functionality for an infinite time. So far, all attempts to generate de novo kefir grain in any fermentation of mixtures of pure starter cultures have failed [37].…”
Section: Generation Of Kefir Grainsmentioning
confidence: 99%
“…It is unclear what causes the microbiota of kefir to form such a stable consortium that maintains its functionality for an infinite time. So far, all attempts to generate de novo kefir grain in any fermentation of mixtures of pure starter cultures have failed [37].…”
Section: Generation Of Kefir Grainsmentioning
confidence: 99%
“…The study of kefir ecosystem may involve the knowledge of the ecology of the grain and its maintenance through centuries as well as the population dynamics of the fermented milk. Comparative analysis of microbial composition of kefir and the corresponding kefir grain showed that both microbial communities are different (Dobson et al 2011;Londero et al 2012;Marsh et al 2013;Kotova et al 2016). Marsh et al (2013) studied 23 kefir grains from different countries (Ireland, the United Kingdom, the United States, Spain, France, Italy, Canada and Germany) and the corresponding fermented milk by high-throughput sequencing of 16S genes.…”
Section: Kefir Micro-organisms In Kefir Grain and In Kefir Fermented mentioning
confidence: 99%
“…Kefir was produced on a laboratory scale in two different treatments, using 200 mL of milk and buttermilk as raw materials accor ding to the methodology described by Kotova et al (2016), with modifications. The skimmed milk and buttermilk were initially heated to 85 ºC during 30 min and then cooled to 22 ºC and inoculated separately with 1.5 % (w/v) kefir grains previously activated.…”
Section: Kefir Productionmentioning
confidence: 99%